The solution of the equation is [tex]x=2[/tex] and [tex]x=-8[/tex]
Explanation:
Given that the equation is [tex]x^{2}+6 x-16=0[/tex]
We need to determine the solution of the equation by completing the square.
Thus, we have,
[tex]x^{2}+6 x-16=0[/tex]
Adding both sides of the equation by 16, we get,
[tex]x^{2}+6 x=16[/tex]
Let us solve by completing the square.
To bring the equation in the form of [tex]x^{2}+2 a x+a^{2}=(x+a)^{2}[/tex], let us add [tex]a^{2}=3^{2}[/tex] to both of the equations.
Thus, we have,
[tex]x^{2}+6 x+3^{2}=16+3^{2}[/tex]
Simplifying, we get,
[tex](x+3)^{2}=25[/tex]
Taking square root on both sides of the equation, we get,
[tex]x+3=\pm5[/tex]
Thus, the two solutions of the quadratic equation are
[tex]x+3=5[/tex] and [tex]x+3=-5[/tex]
Simplifying the two values, we get,
[tex]x=2[/tex] and [tex]x=-8[/tex]
Thus, the roots of the equation are [tex]x=2[/tex] and [tex]x=-8[/tex]